Influence of Strontium phosphate Coating on the Degradation of Physical Vapor Deposition Sprayed Mg Coating on Ti6Al4V Substrate to Promote Bone Tissue Healing - Ibrahim, Muhammad; Yu, Xiaoming; Tan, Lili; Yang, Ke (Frontiers in Materials, 2020)
Ti6Al4V is one of the commonly used orthopedic metallic materials, while its bioactivity is poor, which makes it difficult to produce bone integration between material and bone tissue. In this study a Mg/SrP composite coating was prepared on Ti6Al4V, so as to promote bone tissue healing and shorten the healing cycle. The surface characterization, in vitro degradation performance and bioactivity of the composite coating were investigated and the results revealed that comparing with pure Mg coating, Mg/SrP composite coating has more suitable degradation rate, No cytotoxicity was found on the Mg/SrP composite coated samples, higher proliferation compared with the culture medium was found, indicating that the Mg/SrP composite coating is a candidate coating on Ti6Al4V to improve the bioactivity.